Asset’s Concept Based on Zuhud: Reflection Value of Simplicity in Islam - Nur Alim Bahri; Iwan Triyuwono; Yeney Widya Prihatiningtias (Universitas Muhammadiyah Surakarta, 2021)
This study aims to develop the concept of assets following the principles of Islamic law by incorporating zuhud values. To reach the aim of this study, the researcher used a religionist-spiritualist paradigm with a case study as a research design. Data collection comes from an interview, observation, and documentation. This research found that the concept of the asset based on zuhud is a world of pleasure that aims to make humans loveable by God and other humans, which can provide in-depth knowledge of his humble world in the eyes of Allah, and an understanding of the essential nature of a human being who is always a loving asset that one day will harm him to the very far away.